DAMPAK FOREIGN DIRECT INVESTMENT DAN PERDAGANGAN INTERNASIONAL TERHADAP PERTUMBUHAN EKONOMI NEGARA LOWER MIDDLE INCOME PERIODE 1990-2010 - , GILANG PUTRA RAHMADIAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Various studies related to the role of Foreign Direct Investment (FDI) and international trade to economic growth has been carried out in several countries. However, we need to realize also that the impact of FDI and international trade is not the same from country to country, particularly between developed and developing countries. In the neoclassical growth model, it is also said that the amount of capital and labor have a positive impact on economic growth. This research attempts to analyze the impact between economic growth and inwards FDI, exports, imports, and the amount of capital and labor force in seven lower middle income countries in the period 1990 to 2010 by using panel data analysis tools. The results showed, in general, in the case of lower middle income countries, we found that inwards FDI, exports, and capital are all factors that influence positively, while imports have a negative impact on economic growth in the lower middle income countries. In addition, the export coefficient has a value greater than the coefficient of FDI. In other words, exports have a greater impact on economic growth in the lower middle income countries.